Disruption Management on Harian Jogja’s YouTube Content in Post Pandemic - Pagualand, Anggie Putri Cahyani; Sugiantoro, Hari Akbar (Universitas Muhammadiyah Yogyakarta, 2023)
In the midst of the current development of information technology, mass media is needed to make changes in meeting the need for information and news. There are many phenomena of print media companies that have closed their operations because they are not ready to face technological developments. This development encourages the growth of news media through YouTube in disseminating information, and media management in managing interesting content as a strategy to make this information more accessible to all audiences. The purpose of this research is to find out the post-pandemic management of YouTube content disruption. The theory used is the theory of media convergence. This study uses a qualitative descriptive method using data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the application of content management using media convergence is a necessity to be faster and more effective in following current technological developments. Media convergence affects the performance of journalists in meeting the needs of companies by increasing their skills to meet the needs of media platforms as human resources (HR), by managing interesting content that is needed by the community to become a strategy so that a media can survive and develop amid the development of information technology, one of the implications the economy with media convergence is affecting companies because it changes business behavior and advances companies.